2011
DOI: 10.1016/s0016-5085(11)64178-4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of PRO-Cancer Cytokines in the Plasma Fraction of Stored Packed Red Cells

Abstract: Introduction-Perioperative blood transfusion has been linked to decreased survival in pancreatic cancer; however, the exact causal mechanism has not been elucidated. Allogeneic transfusions are known to expose patients to foreign cells and lipid mediators. We hypothesize that stored packed red cells (pRBCs) contain pro-cancer cytokines that augment tumor progression. We analyzed the plasma fraction of stored pRBCs for pro-cancer cytokines and evaluated the affect of both storage time and leukocyte reduction on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…We postulate that residual WBCs and platelets actively secrete cytokines into RCC supernatants during storage. This hypothesis is consistent with results from a study that showed that tumour necrosis factor‐alpha (TNF‐α) and RANTES (regulated upon activation, normal T cell expressed and secreted) were elevated in fresh RCCs and were thought to promote the progression of cancer following transfusion of fresh RCCs .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We postulate that residual WBCs and platelets actively secrete cytokines into RCC supernatants during storage. This hypothesis is consistent with results from a study that showed that tumour necrosis factor‐alpha (TNF‐α) and RANTES (regulated upon activation, normal T cell expressed and secreted) were elevated in fresh RCCs and were thought to promote the progression of cancer following transfusion of fresh RCCs .…”
Section: Discussionsupporting
confidence: 89%
“…In summary, the immunogenicity of stored RCC products cannot be attributed to only one factor but could be a combination of many. While studies suggest that residual platelets or WBCs are responsible for some of RCC immune modulatory effects , the composition of RCC supernatants in terms of cytokines or other soluble mediators could play a significant role and, could explain lower immunogenicity in young male donors although, this aspect was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, a recent study suggests that cryopreserved PLTs may be immunomodulatory . However, it is important to keep in mind that high concentrations of these molecules have also been associated with adverse consequences, including atherosclerosis, malignancy, and transfusion reactions . As such, future investigations of the functionality of cryopreserved PLTs beyond their hemostatic potential should be initiated.…”
Section: Discussionmentioning
confidence: 99%
“…The storage milieu of erythrocytes can be affected by blood platelets and leucocytes, particularly neutrophilic granulocytes, which predispose to ROS generation . Large amounts of hydroxyl radicals are formed in leucocytes with phagocytic potential during respiratory burst .…”
Section: Introductionmentioning
confidence: 99%